Gnosticism as the beginning of the Western esoteric tradition. Two evidences from the interwar period = Gnostycyzm jako początek zachodniej tradycji ezoterycznej. Dwa świadectwa z okresu dwudziestolecia międzywojennego - Dobkowski, Mariusz (Przegla̜d religioznawczy, 2018)
Author, in connection with his study on the interests in Gnosticism and Manichaeism in Polish non-fiction publications of 1890-1939 period, analyses if Western esotericism in the sources of mentioned period is understood as kind of the esoteric tradition which is opened by Gnosticism. The basis of this research are two evidences from 1926: translation of a book Ewolucja boska. Od Sfinksa do Chrystusa by Édouard Schuré (1841-1929) as well as an article Teozofia w dziejach błędów ludzkich by Marian Morawski (1881-1940). Author, considering this issue, refers also to the Gnostic and anti-Gnostic sources of Late Antiquity.